MATHEMATICAL MODELLING OF THE CENTRIFUGAL COMPRESSOR - Harasymiv, V.; Harasymiv, Т.; Moyseenko, О. (Municipal economy of cities. Series: «Economy science», 2023)
The paper is aimed to create the mathematical model of the centrifugal compressor based on the group method of data handling-type neural networks to determine the compressor volumetric flow rate as the dependence on the centrifugal compressor’s technological parameters (the rotor’s angular velocity, the compressor’s inlet and outlet temperatures, the compressor’s inlet and outlet pressures, the atmospheric pressure). It is the important scientific task, because most centrifugal compressors used in the process industry don’t have equipment needed to measure the volumetric flow rate. It does not allow to estimate the compressor’s technical state during its operation. Verification of the developed model has been performed, based on the 336 data points (collected from the field measurements) and with using the centrifugal compressor of natural gas (16ГЦ2-395/53-76C) of Dolyna linear production administration of gas transmittal pipelines. The test results have been showed the adequate efficiency of the mathematical model.